Những câu hỏi liên quan
TT
Xem chi tiết
SK
6 tháng 2 2022 lúc 15:13

\(\left(x-3\right)\left(x^2+5\right)=0\)

\(\Rightarrow x-3=0\) hoặc \(x^2+5=0\)

      x= 3                   \(x^2=-5\) ( vô lý- do \(x^2\ge0\) với mọi x)

Vậy ...

 

Bình luận (0)
TH
6 tháng 2 2022 lúc 15:15

\(\Rightarrow x-3=0\)

\(\Rightarrow x=3\)

Bình luận (0)
TA
Xem chi tiết
TA
5 tháng 11 2021 lúc 7:56

mình cần gấp  mọi người giúp mình với

Bình luận (0)
LN
5 tháng 11 2021 lúc 7:57

⇒ (x + 1)2 = 16 = (\(\pm4\))2

⇒  \(\left[{}\begin{matrix}x+1=4\\x+1=-4\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=3\\x=-5\end{matrix}\right.\)

Bình luận (0)
TA
Xem chi tiết
PT
5 tháng 11 2021 lúc 8:20

x= -1;1

 

Bình luận (0)
BA
Xem chi tiết
KQ
Xem chi tiết
TT
24 tháng 2 2022 lúc 22:18

\(a)\left(x-2\right)\left(x^2+2x-3\right)\ge0.\)

Đặt \(f\left(x\right)=\left(x-2\right)\left(x^2+2x-3\right).\)

Ta có: \(x-2=0.\Leftrightarrow x=2.\\ x^2+2x-3=0.\Leftrightarrow\left[{}\begin{matrix}x=1.\\x=-3.\end{matrix}\right.\)

Bảng xét dấu:

x                   \(-\infty\)       -3       1       2     \(+\infty\)

\(x-2\)                    -      |    -   |   -   0   +

\(x^2+2x-3\)         +     0    -   0  +   |    +

\(f\left(x\right)\)                     -     0    +  0   -  0   +

Vậy \(f\left(x\right)\ge0.\Leftrightarrow x\in\left[-3;1\right]\cup[2;+\infty).\)

\(b)\dfrac{x^2-9}{-x+5}< 0.\)

Đặt \(g\left(x\right)=\dfrac{x^2-9}{-x+5}.\)

Ta có: \(x^2-9=0.\Leftrightarrow\left[{}\begin{matrix}x=3.\\x=-3.\end{matrix}\right.\)

\(-x+5=0.\Leftrightarrow x=5.\)

Bảng xét dấu:

x            \(-\infty\)      -3       3        5       \(+\infty\)

\(x^2-9\)            +   0   -   0   +   |    +

\(-x+5\)          +    |   +   |    +  0    -

\(g\left(x\right)\)              +    0   -   0   +  ||    -

Vậy \(g\left(x\right)< 0.\Leftrightarrow x\in\left(-3;3\right)\cup\left(5;+\infty\right).\)

Bình luận (0)
AA
Xem chi tiết
H24
12 tháng 4 2023 lúc 0:26

\(2\left(x^2-x\right)-x\left(x+2\right)+4=0\)

\(\Leftrightarrow2x^2-2x-x^2-2x+4=0\)

\(\Leftrightarrow x^2-4x+4=0\)

\(\Leftrightarrow\left(x-2\right)^2=0\)

\(\Leftrightarrow x-2=0\)

\(\Leftrightarrow x=2\)

Vậy \(S=\left\{2\right\}\)

Bình luận (0)
NT
Xem chi tiết
DA
15 tháng 1 2016 lúc 22:37

1.2(x-1)+(x-2)=x-4

         2x-2+x-2=x-4

            2x+ x-x=2+2-4

                    2x=0

=>                  x=0

Vậy x=0

Bình luận (0)
NT
Xem chi tiết
NT
19 tháng 12 2021 lúc 8:43

a: =>x-22=9

hay x=31

Bình luận (0)
TA
Xem chi tiết
NM
5 tháng 11 2021 lúc 7:40

\(\Rightarrow5^2\cdot5^{x+3}=5^6\\ \Rightarrow5^{x+3}=5^4\\ \Rightarrow x+3=4\\ \Rightarrow x=1\)

Bình luận (0)
H24
5 tháng 11 2021 lúc 7:42

\(25.5^{x+3}=5^6\)

\(\Rightarrow5^2.5^{x+3}=5^6\)

\(\Rightarrow5^{x+3}=5^6:5^2\)

\(\Rightarrow5^{x+3}=5^4\)

\(\Rightarrow x+3=4\)

\(\Rightarrow x\)       \(=4-3\)

\(\Rightarrow x\)       \(=1\)

Bình luận (0)